Nutrition‐based interventions to address metabolic syndrome in the Navajo: a systematic review. Issue 21 (2nd August 2015) - Nava, Lorenzo T; Zambrano, Jenelle M; Arviso, Karen P; Brochetti, Denise; Becker, Kathleen L
<x xml:space="preserve">Abstract</x> Aims and objectives The objective of this systematic review is to identify nutrition‐based interventions that may be effective for the prevention and treatment of metabolic syndrome in the Navajo. Background Metabolic syndrome, a major risk factor for cardiovascular disease, affects almost half of the Navajo population. The diet of the Navajo, heavy in fat and refined carbohydrates, has been identified as an important contributing factor to the high rates of metabolic syndrome in this population. Design A search was conducted on PubMed, EMBASE and CINAHL to identify studies published before October, 2013, involving nutrition‐based interventions in adult populations similar to the Navajo targeting at least one measure of metabolic syndrome. Methods Data on efficacy and participation were gathered and synthesised qualitatively. Results Out of 19 studies included in this systematic review, 11 interventions were identified to be effective at improving at least one measure of metabolic syndrome. Level of exposure to the intervention, frequency of intervention activities, family and social support, cultural adaptation and case management were identified as factors that may improve the efficacy of an intervention. Conclusions Multiple nutrition‐based interventions have been found to be effective in populations similar to the Navajo. Relevance to clinical practice Development of a strategy to address metabolic syndrome in the Navajo may involve aspects from multiple interventions to increase efficacy and maximise participation.